Press forming a 0/90 cross-ply advanced thermoplastic composite using the double-dome benchmark geometry - Harrison, P.; Gomes, R.; Curado-Correia, N. (Composites. Part A, Applied science and manufacturing, 2013)
A pre-consolidated thermoplastic advanced composite cross-ply sheet comprised of two uniaxial plies orientated at 0/90° has been thermoformed using tooling based on the double-dome bench-mark geometry. Mitigation of wrinkling was achieved using springs to apply tension to the forming sheet rather than using a friction-based blank-holder. The shear angle across the surface of the formed geometry has been measured and compared with data collected previously from experiments on woven engineering fabrics. The shear behaviour of the material has been characterised as a function of rate and temperature using the picture frame shear test technique. Multi-scale modelling predictions of the material’s shear behaviour have been incorporated in finite element forming predictions; the latter are compared against the experimental results.